3(1-x)=-(7x+5)

Simple and best practice solution for 3(1-x)=-(7x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1-x)=-(7x+5) equation:


Simplifying
3(1 + -1x) = -1(7x + 5)
(1 * 3 + -1x * 3) = -1(7x + 5)
(3 + -3x) = -1(7x + 5)

Reorder the terms:
3 + -3x = -1(5 + 7x)
3 + -3x = (5 * -1 + 7x * -1)
3 + -3x = (-5 + -7x)

Solving
3 + -3x = -5 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
3 + -3x + 7x = -5 + -7x + 7x

Combine like terms: -3x + 7x = 4x
3 + 4x = -5 + -7x + 7x

Combine like terms: -7x + 7x = 0
3 + 4x = -5 + 0
3 + 4x = -5

Add '-3' to each side of the equation.
3 + -3 + 4x = -5 + -3

Combine like terms: 3 + -3 = 0
0 + 4x = -5 + -3
4x = -5 + -3

Combine like terms: -5 + -3 = -8
4x = -8

Divide each side by '4'.
x = -2

Simplifying
x = -2

See similar equations:

| 4(z+2)-7z=6(-0.5z+1)+2 | | 5(5c-1)-1=20c+4 | | 4-3[q]=10 | | 65(2x-5)=180 | | Cos(45+x)=.42cos(45-x) | | 8(4-2.5)=16 | | 11(-3x+2)-2(1-5x)=-7x-6x | | 9(4-2n)-3=4-6(3n-5) | | 3ln(x+2)-5ln(5x)=x | | .6x+5=3 | | -5r-5(5+5r)=-5(2+7r) | | -4.0x+2.7-16x=-4.6x+2.7 | | 2x-160250-160250=320420-160250 | | x^2y-X^2+4y-9=0 | | 8+(-8)=-8-8 | | 17x-4y=29 | | -5(-3.25)=4m+8 | | (2t-5)(6t+1)=(4t-3)(3t+6) | | 2c+3=3-4 | | 4(6.25)+3k=34.60 | | 2x-23+2x-17=8 | | Z^2-(i+1)*z+i=0 | | 5x*9-7=3 | | 12-5(3(-1)+2)=17 | | 9(2n)-3=4-6(3n-5) | | 3x^2-36x-27=0 | | 4m+4+7m=13+8m | | 11(-3x-2)-2(1-5x)=-7x-6x | | 5345+n=288195 | | m+3(4)=7 | | F(-3)=2x+4 | | .66m+2=1m-3 |

Equations solver categories